Wpływ wojennych wydarzeń dziejowych (res gestae) i relacji o nich (historie rerum gestarum) na kondycję materialnych pozostałości po tych wydarzeniach. Studium przypadku na temat dziedzictwa konfliktów zbrojnych jako wyzwania poznawczego i społecznego - Zalewska, Anna Izabella; Cyngot, Dorota (Folia Praehistorica Posnaniensia, 2020)
In the article we consider the relationship between the poor condition of material remains of the Great War on one of the former Eastern Front’s battlefield’s in the Rawka and Bzura region with the long term attitudes of the local population towards the soldiers of Russian and German armies, fighting and killed there. For this purpose, we have analyzed written sources and witnesses accounts, as well asartifacts from archaeological research. We assume that recognizing situation of the local population during the events of 1914–1915 and after the war may bring us closer to answering the questions posed herein. Thus, we suppose, that loss of property, extremely difficult conditions of everyday life, illnesses and suffering, fear of military authorities and soldiers, of epidemic factors and infectious diseases, death of loved ones also those enlisted in the armies of the occupiers – these types of traumatic experiences – conditioned the attitude of the local population towards soldiers of the Great War. Some lasting consequences of this can be observed till today – in the form of fading traces of the material heritage of the Great War. Focusing on the material and discursive dimensions, we analyze the relationships between the primary (res gestae) and consequential/secondary processes (rerum gestarum histories and narrations) and observe a kind of causative “breaking the continuity” between them. Using the methods of historical archaeology, archaeology of recent past, memory studies, history etc., creates interesting, but so far poorly used, research possibilities. Most importantly, it can contribute to shaping attitudes characterized by historical and archaeological sensitivity and the will to understand the value of a difficult heritage (including resting places of fallen soldiers) and to prompt active care for it.